Criminal Action on Traffic Accident-Causing Death Case Study Decision Number 101/Pid.B/2020/PN. Cirebon - Agus Tri Sulistyo (Budapest International Research and Critics University, 2022)
The central review of traffic regulations is to create security, safety, order, and smooth traffic on the roads. Driving a vehicle inadvertently and exceeding the maximum speed, seems to be immature behavior. Most drivers are not aware of the dangers faced when driving a car that exceeds the maximum speed. Not a few drivers commit violations. The purpose of this study is to review criminal law enforcement in terms of legislation and review accountability in cases of traffic accidents that cause the loss of people's lives in traffic accidents in the city of Semarang. This type of juridical normative research. The nature of the research uses descriptive qualitative. The data collection technique uses secondary data (decision Number 101/Pid.B/2020/PN. Cirebon). The results show that the enforcement of the criminal law regarding traffic accidents that result in the loss of people's lives still has several weaknesses and criminal liability has fulfilled the element of criminal responsibility in general.